2020
DOI: 10.1001/jama.2020.18551
|View full text |Cite
|
Sign up to set email alerts
|

A Roadmap to Advance Patient Safety in Ambulatory Care

Abstract: Advances in patient safety in the past 2 decades have focused mainly on inpatient settings, whereas outpatient settings have been relatively overlooked. However, accumulated evidence leaves little justification to continue neglecting ambulatory safety. 1 A systematic review from 2015 estimated that safety incidents, such as those related to administrative and communication issues, missed or delayed diagnoses, and prescribing and medication management errors, occur in median of 2 to 3incidentsper100primarycarev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Given the complexity of general practice, estimating diagnostic errors in primary care is challenging. 26 GPs are often tasked with identifying patients with a serious disease from large numbers who present with common symptoms and mostly benign non-urgent diseases, many of which evolve over time. 27 A significant proportion of face-to-face consultations are for reasons other than making a diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Given the complexity of general practice, estimating diagnostic errors in primary care is challenging. 26 GPs are often tasked with identifying patients with a serious disease from large numbers who present with common symptoms and mostly benign non-urgent diseases, many of which evolve over time. 27 A significant proportion of face-to-face consultations are for reasons other than making a diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Ambulatory patient safety incidents are frequent, with an estimated 2–3 adverse events in every 100 primary care visits. 1 In an AHRQ (Agency for Healthcare Research and Quality)-commissioned technical brief on ambulatory safety, key informants identified six domains of ambulatory safety (medication management, diagnostic errors, care transitions, referrals, culture, and testing) and six strategies used to address these vulnerabilities (communication, health technology, teams, patient engagement, organizational approaches, and measurement). 2 We use this framework to identify the strategies most altered by telemedicine and how those changes impact specific ambulatory safety domains.…”
mentioning
confidence: 99%
“…16 Despite this push for interprofessional education for competency development and increased collaboration among healthcare disciplines, adoption into practice has been slow and inconsistent. 4,17 In higher education, for T he US healthcare system often provides medically complex patients with suboptimal, fragmented care, and a system change to resolve this inadequacy is imperative. [1][2][3] Interprofessional collaboration, in which clinicians from different fi elds work in a unifi ed manner, is an integral component to delivering effi cient, high-quality care, and there is a national push for increased collaborative care in healthcare systems.…”
mentioning
confidence: 99%
“…Despite this push for interprofessional education for competency development and increased collaboration among healthcare disciplines, adoption into practice has been slow and inconsistent 4,17. In higher education, for example, significant workload and suboptimal understanding of the role of other healthcare professionals have been shown to impede the implementation of interprofessional education 18.…”
mentioning
confidence: 99%